2019
DOI: 10.1038/s41598-019-49581-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased regulatory B cells are involved in immune evasion in patients with gastric cancer

Abstract: Accumulating evidence has indicated that immune regulatory cells are involved in the establishment of tumoral immune evasion. However, the role of regulatory B cells (Bregs) in this remains unclear. Here, we identified a role for Bregs in immune evasion in gastric cancer (GC) patients. The frequency of peripheral Bregs was significantly higher in GC patients than in healthy controls (P = 0.0023). Moreover, the frequency of CD19+CD24hiCD27+ B cells in GC tissue was significantly higher than in peripheral blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 26 publications
2
58
0
2
Order By: Relevance
“…Survival analysis showed that five-year OS rates in the Breg Low group were significantly higher than those in the Breg High group. Multivariate analysis revealed that the percentage of Bregs in tumor tissue was an independent prognostic indicator of GC patient survival (50). This study indicates that Breg-related immunosuppression is closely correlated to tumor progression.…”
Section: Potential Of Bregs As Biomarkers and Prognostic Factors Formentioning
confidence: 59%
“…Survival analysis showed that five-year OS rates in the Breg Low group were significantly higher than those in the Breg High group. Multivariate analysis revealed that the percentage of Bregs in tumor tissue was an independent prognostic indicator of GC patient survival (50). This study indicates that Breg-related immunosuppression is closely correlated to tumor progression.…”
Section: Potential Of Bregs As Biomarkers and Prognostic Factors Formentioning
confidence: 59%
“…Tumor-infiltrating mononuclear cells were isolated from 15 GC patients who underwent gastrectomy as previously described [13]. In brief, fresh cancer tissues and non-cancerous gastric mucosa (at least 5 cm apart from the tumor in the resected specimen) were cut into small pieces with a size of approximately 1 mm, and digested with 0.002% DNase I, 0.08% collagenase IV, and 0.01% hyaluronidase (all from Worthington, Lakewood, NJ, USA) at 37°C for 60 min.…”
Section: Isolation Of Tumor-infiltrating Mononuclear Cellsmentioning
confidence: 99%
“…Immunohistochemistry was carried out using samples from 102 patients with stage I-III gastric adenocarcinoma as previously described [13]. Four μm-thick paraffin sections were dewaxed, deparaffinized in xylene, and rehydrated through a graded alcohol series.…”
Section: Immunohistochemistry Assaymentioning
confidence: 99%
“…Tumor-infiltrating mononuclear cells were isolated form 15 GC patients who underwent gastrectomy as previously described [13]. In brief, fresh cancer tissues and non-cancerous gastric mucosa (at least 5 cm apart from the tumor in the resected specimen) were cut into small pieces with a size of approximately 1mm, and digested with 0.002% DNase I, 0.08% collagenase IV, and 0.01% hyaluronidase (all from Worthington, Lakewood, NJ, USA) at 37°C for 60 min.…”
Section: Isolation Of Tumor-infiltrating Mononuclear Cellsmentioning
confidence: 99%
“…Immunohistochemistry was carried out using samples from 102 patients with stage I-III gastric adenocarcinoma as previously described [13]. Four µm-thick paraffin sections were dewaxed, deparaffinized in xylene, and rehydrated through a graded alcohol series.…”
Section: Immunohistochemistry Assaymentioning
confidence: 99%